The coloniality of power in postcolonial Africa: experiences from Nigeria. Issue 5 (5th February 2021) - Fasakin, Akinbode
Abstract: While the coloniality of power underpins the continuity of colonial situations in postcolonial Africa, (neo)liberal thinking attempts to dismiss its place in Africa's contemporary challenges, blaming instead anti-colonial struggles and the quest for complete decolonisation as the cause of these challenges. A focus on this neoliberal cum pro-colonial perspectives, at the expense of a corpus of post-, anti- and de-colonial writings that expose and challenge coloniality, however, inhibits our understanding of the consolidation, problematic place and impact of the coloniality of power in postcolonial Africa. Analysing the presence of colonial situations in policy choices and governance patterns, which link Africa's postcolonial present to their colonial past, this paper claims that the coloniality of power retains its salience in postcolonial Africa. Illustrating with experiences from Nigeria, I show how this continues to structure the state of affairs in Africa even after formal colonialism has ended. This article contributes to the discourse on the legacies of colonialism in Africa.